2015
DOI: 10.3389/fchem.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among ergot alkaloids, cytochrome P450 activity, and beef steer growth

Abstract: Determining a grazing animal's susceptibility to ergot alkaloids has been a research topic for decades. Our objective was to determine if the Promega™ P450-Glo assay could be used to indirectly detect ergot alkaloids or their metabolites in urine of steers. The first experiment validated the effects of ergot alkaloids [0, 20, and 40 μM of ergotamine (ET), dihydroergotamine (DHET), and ergonovine (EN)] on human CYP3A4 using the P450-Glo assay (Promega™ V9800). With this assay, luminescence is directly proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Vasoconstrictive responses (Klotz et al, 2008;Oliver et al, 1993;Oliver et al, 1998;Rhodes et al, 1991) inducing perturbed nutrient absorption and metabolism (Egert et al, 2014a;Pesqueira et al, 2014) occur concurrently with altered circulating prolactin and cholesterol levels, which together with and intra-and extrahepatic enzyme activity changes, may play a role in the etiology of FT (Bacon, 1995;Rosenkrans and Ezell, 2015;Settivari et al, 2008;Thompson and Stuedemann, 1993;Zbib et al, 2014Zbib et al, , 2015. Foote et al (2013) suggested impaired weight gain might be attributed to a decrease in volatile fatty acid (VFA) absorption or production caused by increased ruminal EA concentration.…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…Vasoconstrictive responses (Klotz et al, 2008;Oliver et al, 1993;Oliver et al, 1998;Rhodes et al, 1991) inducing perturbed nutrient absorption and metabolism (Egert et al, 2014a;Pesqueira et al, 2014) occur concurrently with altered circulating prolactin and cholesterol levels, which together with and intra-and extrahepatic enzyme activity changes, may play a role in the etiology of FT (Bacon, 1995;Rosenkrans and Ezell, 2015;Settivari et al, 2008;Thompson and Stuedemann, 1993;Zbib et al, 2014Zbib et al, , 2015. Foote et al (2013) suggested impaired weight gain might be attributed to a decrease in volatile fatty acid (VFA) absorption or production caused by increased ruminal EA concentration.…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…Bovine CYP3A (bCYP3A) enzymes are involved in the metabolism of a number of drugs widely used in farming such as the macrocyclic lactone moxidectin 19 , tiamulin and macrolide antibiotics 20 as well as the ionophore monensin 21 . Moreover, bCYP3As are involved in the bioactivation of important natural toxins like aflatoxins and ergot alkaloids 22,23 . Three main b CYP3A genes have been identified, and a new nomenclature, mirroring the true evolutionary relationships among bCYP isoforms has been proposed: CYP3A28 (orthologue of human CYP3A4 ), CYP3A38 (orthologue of human CYP3A5 ) and CYP3A48 (corresponding to “b CYP3A4 nifedipine oxidase”) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they are responsible for the bioactivation of natural toxins of current growing interest, i.e. aflatoxins and ergot alkaloids (Kuilman et al 2000;Sales et al 2012;Rosenkrans and Ezell 2015).…”
Section: Introductionmentioning
confidence: 99%